Engagement Rules That Underpin DBL-DARC Interactions for Ingress of Plasmodium knowlesi and Plasmodium vivax Into Human Erythrocytes - Yogavel, Manickam; Chhibber-Goel, Jyoti; Jamwal, Abhishek; Gupta, Swati; Sharma, Amit (Frontiers in Molecular Biosciences, 2018)
Malaria parasite erythrocytic stages comprise of repeated bursts of parasites via cyclical invasion of host erythrocytes using dedicated receptor-ligand interactions. A family of erythrocyte-binding proteins from P. knowlesi and P. vivax attach to human Duffy antigen receptor for chemokines (DARC) via their Duffy binding-like domains (DBLs) for invasion. Here we provide a novel, testable and overarching interaction model that rationalizes even contradictory pieces of evidence that have so far existed in the literature on Pk/Pv-DBL/DARC binding determinants. We further address the conundrum of how parasite-encoded Pk/Pv-DBLs recognize human DARC and collate evidence for two distinct DARC integration sites on Pk/Pv-DBLs.